Flavor tagged time-dependent angular analysis of the Bs0 →J/ψφ decay and extraction of ΔΓs and the weak phase φs in ATLAS - Alconada Verzini, María Josefina (2014)
A measurement of the Bs0→J/ψφ decay parameters, updated to include flavor tagging is reported using 4.9fb-1 of integrated luminosity collected by the ATLAS detector from s=7TeV pp collisions recorded in 2011 at the LHC. The values measured for the physical parameters are φs=0.12±0.25(stat)±0.05(syst)rad ΔΓs=0.053±0.021(stat)±0.010(syst)ps-1 Γs=0.677±0.007(stat)±0.004(syst)ps-1 |A (0)|2=0.220±0.008(stat ±0.009(syst) |A0(0)|2=0.529±0.006(stat)±0.012(syst) δ=3.89±0.47(stat)±0.11(syst)rad where the parameter ΔΓs is constrained to be positive. The S-wave contribution was measured and found to be compatible with zero. Results for φs and ΔΓs are also presented as 68% and 95% likelihood contours, which show agreement with the Standard Model expectations.